(untitled) (Research, Society and Development, 2021)
The objective of this review was to address the main factors that affect the morphogenic and structural characteristics of forage plants. Within the Brazilian agricultural system, there is a predominance of livestock on pasture. Due to the favorable conditions of the national territory, it is possible to produce several species of forage plants. In this sense, understanding the behavior of the forage ecosystem in the face of variations in natural resources becomes a tool capable of assisting in the development of sustainable management goals. Morphogenesis is used to measure the appearance and expansion of plant organs through the flow of tissues that occur within the forage canopy. In general, the structural characteristics of a forage canopy, depends on the morphogenic characteristics of the species, which are genetically determined. However, these characteristics are directly influenced by abiotic and biotic factors that alter the growth pattern of these plants. Furthermore, through the evaluation of the morphogenetic processes involved in the pasture ecosystem, it is possible to develop goals for the sustainable management of the forage canopy, contributing to increase the productivity of agricultural systems in Brazil.